Influence of PEDOT:PSS Coating Thickness on the Performance of Stimulation Electrodes. Issue 16 (22nd June 2020) - Dijk, Gerwin; Ruigrok, Hermanus J.; O'Connor, Rodney P.
Abstract: Poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) is a conducting polymer commonly used to coat the electrodes of biomedical devices to reduce impedance and improve charge injection. The stimulation performance of such electrodes depends on coating thickness due to the volumetric properties of the conducting polymer. Here, the influence of PEDOT:PSS coating thickness on impedance, charge injection, and electrode stability is examined. The results show that stacking spin‐coated layers is a reliable method to control coating thickness without introducing electronic or ionic blocking elements in between layers. Besides improving the polymer‐electrolyte interaction due to a higher capacitance, thicker coatings can endure more stimulation pulses and withstand higher voltages without loss of performance, thus enhancing the lifetime of the electrode. This work presents fundamental insights into the coupling of PEDOT:PSS coated electrodes with electrolytes and provides guidance in the development of organic bioelectronic stimulation devices for optimum performance and longevity. Abstract : Electrodes coated with various poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate thicknesses are studied. Thicker coatings result in a lower electrode impedance, higher charge injection, and improved stability. However, most of the performance parameters saturate as a function of thickness. The optimum‐coating thickness depends on the specific application and should be chosen accordingly.